The pedagogical action as Practical reason: observations on Lectures about Takes of Wise (Jena 1794) - Cordero Redondo, Joan Javier (Anales del Seminario de Historia de la Filosofía, 2026)
The work studies the elements that make up the pedagogical thinking in the book “Lectures about Takes of Wise”. Some biographical notes are made, which provide support and origin to the construction of this philosophical thinking regarding education, as well as the characteristics of pedagogical and formative thinking for the improvement and perfection of humankind. It is concluded that Fichte’s educational thinking involves cultural and social exchange and an ethical intersubjective relationship. Reciprocity is a rational activity associated with pedagogy and the expansion of the practical dimension of freedom.
Keywords: Fichte; Kantianism; pedagogy; practical reason; education